A prática do teatro do oprimido no ensino de filosofia - Rocha, Paulo André Menezes da (2023)
Teaching Philosophy in a philosophical manner, enabling the theory to be experienced by students, was the challenge that motivated the research embodied in this dissertation and its resulting product, which aims to introduce the practice of Theatre of the Oppressed in the teaching of Philosophy, providing learning through conceptual experience. The investigation was based on Augusto Boal's Theatre of the Oppressed, using its techniques to transform spectators into spect-actors, as for Boal, theater is a weapon of liberation and rehearsal for life. The theoretical foundation of the experimentation of concepts is based on Deleuze and Guattari (1992), who argue that Philosophy is the creation of concepts, and Bondía (2002), who presents experience as something that happens to us. To support the argument that Philosophy classes should be meaningful and based on students' experiences, we turned to theorists such as Freire (1987), Gallo (2012), Cerletti (2009), and Gelamo (2009). As part of the methodological procedures, classes were conducted that transformed the student-participant-spectators into student-actor-participants. The action research, following Thiollent (1986), took place at EEMTI Romeu de Castro Menezes in an elective course with 22 students, who, after experiencing the entire transformation from spectator to spect-actor, were invited to respond to a questionnaire, the answers of which were analyzed from the perspective of Bardin's (1977) content analysis. The responses provided by the student-philosopher-spect-actors to the questionnaire, as well as the dialogues, reflections, and accounts of their experiences, allow us to affirm that the Theatre of the Oppressed can and should be used as a powerful tool in the teaching of philosophy, capable of providing an experience with concepts and contributing to a philosophically oriented philosophy education. The product of this research is the didactic guide Philosophizing with the Theatre of the Oppressed, a contribution to the teaching of Philosophy.